An Improvement Object Detection Method Findcontour with Fuzzy Logic for Detect Balinese Script Object - Ida Bagus Putra Manuaba; Komang Ayu Triana Indah; Muhammad Fahmi; Irma Nuraeni Salsabila (Pandawan, 2022)
The function of OpenCV can be used as a method for detecting Balinese script objects . Experiments to detect Balinese script using this function are able to detect all objects that are on palm leaf media. Objects that have been detected are literal objects and non-literal objects. This study aims to improve the detection method with the findcontour function by adding a fuzzy algorithm, to separate Balinese script objects from non-Balinese characters. The data in this study were in the form of Balinese script written on palm leaves. The Balinese manuscripts used as data in the research are new manuscripts that were deliberately written for research purposes. Fuzzy logic in this study is used to determine objects that have been detected, including script objects or not. The results are visible from the detected objects, fuzzy logic is able to eliminate 400 - 5000 objects that are not needed. Meanwhile, in terms of time, the filtering process with fuzzy logic has an impact on the ROI process being faster with an average time of less than 1 second.